2015
DOI: 10.3390/molecules20022100
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of the Uncaria Hook Alkaloid Geissoschizine Methyl Ether in Rat and Human Liver Microsomes Using High-Performance Liquid Chromatography with Tandem Mass Spectrometry

Abstract: Geissoschizine methyl ether (GM) is an indole alkaloid found in Uncaria hook, which is a galenical constituent of yokukansan, a traditional Japanese medicine. GM has been identified as the active component responsible for anti-aggressive effects. In this study, the metabolic profiling of GM in rat and human liver microsomes was investigated. Thirteen metabolites of GM were elucidated and identified using a high-performance liquid chromatography with tandem mass spectrometry method, and their molecular structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In vitro studies using rat and human liver microsomes reported that GM was metabolized into at least 13 metabolites including hydroxylated, dehydrogenated, hydroxylated + dehydrogenated, demethylated, and hydration forms by several CYP isoforms, and CYP3A4 was found to mainly contribute to GM metabolism [ 58 , 59 ]. Parent/unchanged GM was detected in both plasma and brain of rats after orally administered YKS, and demonstrated that GM was able to cross the blood-brain barrier (BBB) in an in vitro BBB assay [ 13 , 14 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In vitro studies using rat and human liver microsomes reported that GM was metabolized into at least 13 metabolites including hydroxylated, dehydrogenated, hydroxylated + dehydrogenated, demethylated, and hydration forms by several CYP isoforms, and CYP3A4 was found to mainly contribute to GM metabolism [ 58 , 59 ]. Parent/unchanged GM was detected in both plasma and brain of rats after orally administered YKS, and demonstrated that GM was able to cross the blood-brain barrier (BBB) in an in vitro BBB assay [ 13 , 14 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Earlier publications have described methods, including high-performance liquid chromatography with ultra-violet detection [21], high-performance liquid chromatography with DAD detection [22], and high-performance liquid chromatography-electrospray ionization-tandem mass spectrometry [23,24] that have been used in the qualitative or quantitative analysis of alkaloids from the genus Coptis, single herb or herbs used together in couples (Coptis-Evodia herb couple [25], scutellaria-coptis herb couple [26]), at most six or seven alkaloids simultaneously. However, to date, there are few publications concerning CCY , especially the pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the YKS-alone group, the peak concentrations of GM in the plasma (Figure 1B) and brain (Figure 1F) of the MEM + YKS-combined group tended to be increased (approximately 40% and 40% in the plasma and brain), although the time-dependent changes in GM concentrations between both groups were not statistically significant (two-way ANOVA, group factor: F 1, 25 = 2.98, p = 0.096 in the plasma; and F 1, 25 = 4.09, p = 0.054 in the brain). In addition to this result, GM has been reported to be metabolized into several metabolites in rats and humans [29,30], and its metabolism is performed mainly by CYP3A4 in humans [30]. On the other hand, an in vitro study has been showed that MEM does not induce or inhibit the activity of CYPs, epoxide hydrolase, flavin-containing monooxygenase, and UDP-glucuronosyltransferase [1].…”
Section: Resultsmentioning
confidence: 99%
“…MEM is almost entirely excreted in the urine via organic cation transporter 2 [28]. On the other hand, not all metabolites of ingredients in YKS are known, and in vitro studies using rat and human liver microsomes have reported that GM is metabolized into several metabolites in both species [29,30]. Furthermore, cytochrome P450 (CYP) 3A4 was shown mainly to contribute to GM metabolism in human liver microsomes [30].…”
Section: Introductionmentioning
confidence: 99%